Pengembangan Model Kurikulum Pendidikan Agama Islam Berbasis Multikultural - Haj, Habil Syahril; Marno, Marno (ISLAMIKA, 2024)
In the context of globalization and cultural diversity, religious education needs to accommodate societal diversity to remain relevant and inclusive. This research employs a curriculum development approach to design a model that integrates Islamic values with the concept of multiculturalism, aiming to develop a Multicultural-Based Islamic Religious Education curriculum. The methodology utilized a qualitative approach through interviews, observations, and document analysis. The findings of the research emphasize the importance of a multicultural-based Islamic religious education curriculum, given that Indonesia is a diverse nation comprising various ethnicities, languages, religions, and cultures. Implementing a multicultural-based Islamic religious education curriculum is expected to have a positive impact on fostering harmony and tolerance among individuals.